Frommer's Argentina - Luongo, Michael. 4 0 16; O'Malley, Charlie.;Pashby, Christie; 5 (Hoboken, NJ : Wiley Publishing, Inc., 2007)
Presents guidance and tools for visitors to Argentina, including trip planning information, itineraries, lodging and dining suggestions for different budgets, and details on history, culture, and things to see and do.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; 20; Argentina;Argentina -- Guidebooks.;Guidebooks.; 2